THE ROLE OF OYBEK’S CREATIVITY IN THE DEVELOPMENT OF ARTISTICITY OF NAVOI (Scientific journal of the Fergana State University, 2024)
The article is devoted to the study of scientific articles by Musa Tashmuhammad Oybek about the life and work of the great thinker Alisher Navoi. Aibek's contribution to the development of Navoi studies is shown. The contents of these articles are explained. A non-standard study of Oybek’s life and work in the classroom increases students’ interest in the lesson and contributes to an in-depth mastery of the subject. This article describes the study of Oybek’s life and work based on new methods.